Revisiting the implementation of Independent and Cambridge Curriculum in English Subject for Secondary Education; A Case Study in an Islamic Public School in Batam - Arya Putra Lievi Darwan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This research seeks to explore the implementation of the Merdeka Curriculum alongside the Cambridge International Curriculum in the English subject at MAN Insan Cendekia Batam, focusing specifically on the integration of Islamic values into teaching. Using a qualitative case study method, data were gathered through semi-structured interviews and rubric evaluation to understand instructional techniques, evaluation methods, and value incorporation in depth. The results show that English educators successfully integrate the dual curriculum through the use of student-focused, practical activities like job application tasks and interview practice, which enhance communicative skills and personal growth. Islamic values were not just explicitly taught but also integrated seamlessly into classroom practices, promoting comprehensive development. In spite of obstacles like managing curriculum requirements, varying student skill levels, and relating global topics to local contexts, the research emphasizes effective strategies such as gradual scaffolding, teamwork in learning, and innovative lesson design. The research finds that intentional curriculum development and reflective instruction can facilitate the effective execution of dual curricula in Islamic public schools, enhancing both global preparedness and spiritual authenticity. Keywords: Merdeka Curriculum, Cambridge International Curriculum, English Language Teaching, Islamic Values, Curriculum Integration, 21st-Century Skills, Islamic Public School